2021
DOI: 10.1002/ieam.4474
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment in PM10‐bound trace elements, seasonal patterns, and source apportionment study in a critically polluted coking coalfield area of India

Abstract: Jharia Coalfield (JCF) has been affected by coalmine fire and subsidence problems for several years. The emission of particulate pollutants is due to the history of unscientific and unregulated coal mining in the JCF area. In the present study (conducted in the year 2019), seasonal variations, possible causes, and human health hazards of particulate matter (PM10)‐bound trace metals like Cd, Cu, Fe, Cr, Ni, Mn, Co, Pb, Zn, and As were estimated. The mean concentration of PM10 (418 ± 67 µg/m3) exceeded the limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…On one hand, extensive studies have revealed that haze pollution is an atmospheric environmental phenomenon that causes a significant decrease in visibility. It is generally believed that its formation cause and mechanism are very complicated, because the material sources are extensive, and its promoting conditions and spatiotemporal evolutionary processes are dynamically changeable (Hyslop, 2009; Singh & Singh, 2022; Ye et al, 2003). However, previous studies have failed to construct a consensus conceptual model that comprehensively reflects the substance origins, promoting conditions, and inner attributes of regional haze pollution (Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, extensive studies have revealed that haze pollution is an atmospheric environmental phenomenon that causes a significant decrease in visibility. It is generally believed that its formation cause and mechanism are very complicated, because the material sources are extensive, and its promoting conditions and spatiotemporal evolutionary processes are dynamically changeable (Hyslop, 2009; Singh & Singh, 2022; Ye et al, 2003). However, previous studies have failed to construct a consensus conceptual model that comprehensively reflects the substance origins, promoting conditions, and inner attributes of regional haze pollution (Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%